2018
DOI: 10.37358/rc.18.4.6228
|View full text |Cite
|
Sign up to set email alerts
|

Laser Therapy Evaluation in Complications of Restorations by Total-Etch Technique

Abstract: The aim of this study was to evaluate the efficiency of laser therapy in post-operative sensitivity by Visual Analogue Scale (VAS) to the 57 patients after restoration with two different resins composite. In the first group (28 patients, 30 teeth) it was restored the cavity class I Black with micro-hybrid composite Filtek Z250 - Adper Single Bond (3M/ESPE). In the second group (29 patients, 30 teeth) it was restored the cavity class III Black with nano-hybrid composite Ceram X One Sphere Tec-Prime and Bond One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…LLLT was also introduced in the treatment of dentine hypersensitivity due to the slow onset of action of the traditional desensitizing agents. It has been suggested that LLLT decreases dental hypersensitivity pain by stimulating the stimulation of endorphin and nitric oxide production, by inhibition of C-fiber afferent nerve depolarization as well as the decrease of bradykinin levels [20,21]. Laser therapy is sustained by literature data that indicates conflicting results from the laser related researches, but a slight clinical advantage of laser therapy over topical desensitizing agents [21].…”
mentioning
confidence: 99%
“…LLLT was also introduced in the treatment of dentine hypersensitivity due to the slow onset of action of the traditional desensitizing agents. It has been suggested that LLLT decreases dental hypersensitivity pain by stimulating the stimulation of endorphin and nitric oxide production, by inhibition of C-fiber afferent nerve depolarization as well as the decrease of bradykinin levels [20,21]. Laser therapy is sustained by literature data that indicates conflicting results from the laser related researches, but a slight clinical advantage of laser therapy over topical desensitizing agents [21].…”
mentioning
confidence: 99%
“…Vital abutments become extremely sensitive after their preparation to stimuli as warmth, cold, pressure, and brushing may become painful [50]. Usually one the therapeutically strategies for post-operative sensitivity is the prescription of analgesic medication, aiming to ameliorate or eliminate the pain [51]. The general scientific consensus is that through occluding the exposed dentinal tubules, effectively is relieved the occasional pain of affected teeth and of vital abutments [52].…”
Section: Resultsmentioning
confidence: 99%
“…In the conditions in which the mother presents a high caries risk often highlighted in many specialized studies [13,14] and evaluated according to criteria for establishing it, this method is highly recommended. Prevention is aimed at all age groups, but the numerous studies on geriatric patients orally rehabilitated complex orient us towards the indication and application of these materials as early as possible [15].…”
Section: Resultsmentioning
confidence: 99%